2017
DOI: 10.1111/rda.13096
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the MAPK kinase inhibitor U0126 during the first two hours of in vitro maturation improves bovine oocyte developmental competence

Abstract: This study examined the effects of treatment with U0126, which inhibits MAPK by inhibiting MAPK kinase, during the first 2 hr of in vitro maturation on bovine developmental competence and on gap junction (GAPJ) communication between the oocyte and cumulus cells. The percentage of oocytes developing to the blastocyst stage in the group treated with 5 μM U0126 (28%) was significantly higher than that in controls (15%, p < .05), while that in the group treated with 10 μM U0126 (18%) was not. Breakdown of the GAPJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…At the last stage of folliculogenesis, MAPK is stimulated by LH through the ERK-MAPK signaling pathway and promotes GJA1 phosphorylation [33]. With GJA1 phosphorylation, the gap junction is lost, which decreases the concentration of cGMP (cyclic guanosine monophosphate) in oocytes and promotes the process of meiosis [34][35][36]. cAMP (cyclic adenosine monophosphate), a second messenger, has been known to induce oocyte meiotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…At the last stage of folliculogenesis, MAPK is stimulated by LH through the ERK-MAPK signaling pathway and promotes GJA1 phosphorylation [33]. With GJA1 phosphorylation, the gap junction is lost, which decreases the concentration of cGMP (cyclic guanosine monophosphate) in oocytes and promotes the process of meiosis [34][35][36]. cAMP (cyclic adenosine monophosphate), a second messenger, has been known to induce oocyte meiotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…In porcine oocytes, it was demonstrated that Cx43 is highly controlled by gonadotropins [ 59 , 60 ]. Thereby, the decrease in the concentration of cGMP in oocytes induces hydrolysis of cAMP, which promotes the meiotic process and maturation of oocytes [ 61 ].…”
Section: Pannexin and Connexin Involvement In Oocyte Maturationmentioning
confidence: 99%
“…Activation of the EGF/EGFR signaling cascade increases the expression of MAPK, which promotes the phosphorylation of connexin 43 (GJA1), causing the closure of gap junctions (11). On the other hand, activated EGFR also inhibits the production of cyclic guanosine monophosphate (cGMP) and suppresses meiosis (13). This is because cGMP triggers meiosis in oocytes by inhibiting the hydrolysis of cyclic adenosine monophosphate (cAMP).…”
Section: Introductionmentioning
confidence: 99%